IDENTIFIKASI LAPISAN PENYEBAB LONGSOR MENGGUNAKAN GROUND PENETRATING RADAR AREA MONUMEN PESAWAT SANGATTA PT. KALTIM PRIMA COAL - Marbun, Meyliza Cronika; Supriyanto, Supriyanto; Rinaldi, Aditya (Geophysics Study Program, Faculty of Mathematics and Natural Sciences, Mulawarman University, 2020)
A landslide is an event where a mass of rock, soil or a mixture of rock and soil are moved as a slope. One of the mechanical properties that can be a trigger of landslides is the reduction in rock shear strength. In this research, the authors used the Geophysical method that is Ground Penetrating Radar (GPR), by utilizing different dielectric properties of rocks when given electromagnetic wave propagation to see the amplitude contrast in the recorded data as an approach to the type of rock lithology and rock layers below the soil surface so that it can be used to identify layers that cause landslides. The frequency of GPR that used in this research is 40 MHz. The research aims to determine the type of layer that causes landslides in the area of ​​Sangatta Aircraft Monument, PT. Kaltim Prima Coal. The results of this research are in the form of GPR data which is correlated with the carrying capacity of the soil so that the avalanche causing layer in the study area is sandy clay layer.